From nano-emulsions to phase separation: evidence of nano-segregation in (alkane plus perfluoroalkane) mixtures using Xe-129 NMR Spectroscopy - Morgado, Pedro; Martins, Luís F. G.; Filipe, Eduardo J. M. (Royal Society of Chemistry, 2019)
In this work we demonstrate that mixtures of (hexane + perfluorohexane) above the upper critical solution temperature segregate by forming domains at the nanometric scale. 129Xe NMR spectra obtained for solutions of xenon in liquid mixtures of (hexane + perfluorohexane) as a function of temperature suggest the existence of domains richer in the hydrogenated component, in which xenon “prefers” to be solvated. The average local concentration within the xenon coordination sphere is at least 0.05 higher in hexane mole fraction than the nominal concentration of the mixture. Atomistic molecular dynamics simulations support this analysis in excellent agreement with the experimental data. Additionally, 129Xe NMR spectra in pure perfluoroalkanes allow a detailed analysis of the liquid structure, continuing that previously reported for the liquid alkanes. It should be emphasised that nano-segregation is here observed in fluids governed exclusively by dispersion interactions, in contrast to other examples in which hydrogen bonding and polarity play important roles. Given its simplicity, this case study is thus prone to have a general impact in understanding the early mechanisms of segregation, phase separation and self-assembly.